The concept of socio-political contract and its development in the experience of early political Islam - M. G. Almheiri, Hamda Ghalib; Shuriye, Abdi Omar (Center for Promoting Ideas, USA, 2018)
This research aims at providing an intellectual study to justify or refute the accusation that says,“Islam established its empire by sword and its system of government was undemocratic, but purely based on autocracy and theocracy”,by studyingthe social and political system of Arabs before and after Islam; how did Islam influence their system of life morally and politically? This research confirmed that Islam came and met Arabs on some peculiar customs and traditions, such as racism, fanaticism, partisanship, etc., those acts that werehighly requiredurgent rectification and amendment, and indeed that was what Islam as a new administration tackled with different approaches based on wisdom and social agreements.The research figured out that the establishment of Islamic state was primarily based on mutual consultation and agreement between Prophet (SAW) and the people of al-Madīdah, as it is proven by the first and second treaties signed between both parties, which can be considered as Socio-Political Contract andfactors of good citizenship. Furthermore, upon arrival of Prophet Muhammad in Madinah he started with the main factors of stability, harmony, security and peaceful co-existence with others, by regulating the terms of relationship between the citizens of al-Madinah, who wereformed from different ethnics and religious groups, in a document that can be considered as al-Madinah’s constitution in 623 A.D. The document that contained the statement and explanation of the duties and rights of every group including Muslims and others. The research concluded that the theory of governance and formation of the state and social institutions in Islam was based on mutual consultation and agreement between the concerned parties, as it was manifest through the treaties signed by Muhammad (SAW), his administration, as well as his caliphs’ administration.The basis of the theory of governance in Islam is celestial in terms of the legislative power and decree’s right, which are the prohibitions and lawfulness; this is strictly limited to Allah and his messenger. However, the executive and judicial rights are given to the public, based on their favourite system of government as well as their Ijtihad on the system of application for the better establishment of justice.